ASPECTS REGARDING THE TOP-DOWN DESIGN AND THE TRANSFER OF PROJECTS TO THE BENEFICIARY - Adrian Mihai GOANTA; Diana Gina MUSCA; Aurora Maria POTIRNICHE; Gigel Florin CAPATANA (Journal of Industrial Design and Engineering Graphics, 2024)
The paper presents some aspects of the evolution made by computer-aided design and the presentation of some common commands used in Inventor 2024. In addition, both the Any CAD import method and the transfer methods offered by the Autodesk Inventor Professional 2024 version are presented. At the end of the work, some results obtained using the educational versions downloaded for university users at the level of diploma or dissertation work are presented.